Deregulation of microRNA-181c in cerebrospinal fluid of patients with clinically isolated syndrome is associated with early conversion to relapsing–remitting multiple sclerosis. (August 2016) - Ahlbrecht, Jonas; Martino, Filippo; Pul, Refik; Skripuletz, Thomas; Sühs, Kurt-Wolfram; Schauerte, Celina; Yildiz, Özlem; Trebst, Corinna; Tasto, Lars; Thum, Sabrina; Pfanne, Angelika; Roesler, Romy; et al.
Background: MiRNA-181c, miRNA-633 and miRNA-922 have been reported to be deregulated in multiple sclerosis. Objectives: To investigate the association between miRNA-181c, miRNA-633 and miRNA-922 and conversion from clinically isolated syndrome (CIS) to relapsing–remitting multiple sclerosis (RRMS); and to compare microRNAs in cerebrospinal fluid (CSF) and serum with regard to dysfunction of the blood–CSF barrier. Methods: CSF and serum miRNA-181c, miRNA-633 and miRNA-922 were retrospectively determined by quantitative real-time polymerase chain reaction in CIS patients with (CIS-RRMS) and without (CIS-CIS) conversion to RRMS within 1 year. Results: Thirty of 58 CIS patients developed RRMS. Cerebrospinal fluid miRNA-922, serum miRNA-922 and cerebrospinal fluid miRNA-181c were significantly higher in CIS-RRMS compared to CIS-CIS ( P =0.027, P =0.048, P =0.029, respectively). High levels of cerebrospinal fluid miRNA-181c were independently associated with conversion from CIS to RRMS in multivariate Cox regression analysis (hazard ratio 2.99, 95% confidence interval 1.41–6.34, P =0.005). A combination of high cerebrospinal fluid miRNA-181c, younger age and more than nine lesions on magnetic resonance imaging showed the highest specificity (96%) and positive predictive value (94%) for conversion from CIS to RRMS. MiRNA-181c was higher in serum than in cerebrospinal fluid ( P <0.001), while miRNA-633 and miRNA-922 were no different in cerebrospinal fluid and serum. Cerebrospinal fluid/serum albumin quotients did not correlate with microRNAs in cerebrospinal fluid (all P >0.711). Conclusions: Cerebrospinal fluid miRNA-181c might serve as a biomarker for early conversion to RRMS. Moreover, our data suggest an intrathecal origin of microRNAs detected in the cerebrospinal fluid.